Glycyrrhetinic acid binds to the conserved P-loop region and interferes with the interaction of RAS-effector proteins - Yuan Zhang; Zhihua Wang; Xiaoyao Ma; Shengnan Yang; Xueyan Hu; Jin Tao; Yuanyuan Hou; Gang Bai (Elsevier, 2019)
Members of the RAS proto-oncogene superfamily are indispensable molecular switches that play critical roles in cell proliferation, differentiation, and cell survival. Recent studies have attempted to prevent the interaction of RAS/GTP with RAS guanine nucleotide exchange factors (GEFs), impair RAS-effector interactions, and suppress RAS localization to prevent oncogenic signalling. The present study aimed to investigate the effect of the natural triterpenoic acid inhibitor glycyrrhetinic acid, which is isolated from the roots of Glycyrrhiza plant species, on RAS stability. We found that glycyrrhetinic acid may bind to the P-loop of RAS and alter its stability. Based on our biochemical tests and structural analysis results, glycyrrhetinic acid induced a conformational change in RAS. Meanwhile, glycyrrhetinic acid abolishes the function of RAS by interfering with the effector protein RAF kinase activation and RAS/MAPK signalling. KEY WORDS: Glycyrrhetinic acid, RAS, Allosteric inhibitor, RAS/MAPK signalling